Strategic Efforts to Improve the Professionalism of Honorary Teachers - Fauzi, Anis; Mu’in , Abdul; Kulsum, Umi; Ghanib , Muhammad Faizal A. (Journal of Islamic Education Research, 2025)
This study examined the welfare and professional development of honorary teachers in Cilegon City, as well as the strategic efforts undertaken by the local education office to enhance their conditions. Using a qualitative approach, the researchers collected data through participant observation, in-depth interviews, document and media analysis, and triangulation. The data analysis followed four stages: data collection, reduction, presentation, and validation. The findings revealed that while most honorary teachers demonstrated adequate teaching competencies, significant challenges remained in terms of welfare and recognition. Strategic efforts, including training programs, motivational initiatives, improved supervision, and performance-based incentives, have been implemented to foster professional growth. However, constraints such as limited budget allocations and inconsistent policy implementation hinder broader progress. The study concludes that strengthening support systems and increasing budgetary commitment are crucial to sustainably improving the welfare and professionalism of honorary teachers.